The Concept of Sakinah and the Quality of Early-Age Marriage Among Young Couples in Mojosari Village, Puger District, Jember Regency - Baihaki, Ahmad; Zionis, Rijal Mumazziq (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study examines the concept of sakinah and its influence on the quality of early marriage among young couples in Mojosari Village, Puger District, Jember Regency, as well as its impact on household life. Early marriage is often viewed negatively due to assumptions that couples are not yet prepared psychologically, economically, and socially. However, field findings show that some young couples are able to build a sakinah family through mutual understanding, acceptance of each other’s shortcomings, fulfilling responsibilities according to their roles, and receiving support from both family and the surrounding community. This research adopts a descriptive qualitative approach using observation and in-depth interviews with five early-married couples. The results indicate that household resilience based on the sakinah concept can be achieved when there is mutual commitment, effective communication, and the application of Islamic values as a guide to life. With mental and spiritual readiness, early marriage can be experienced positively and contribute to the formation of a stable and harmonious family. This study affirms that readiness not merely age is the key to achieving a quality marriage. [Penelitian ini membahas konsep sakinah terhadap kualitas pernikahan usia dini pasangan muda di Desa Mojosari, Kecamatan Puger, Kabupaten Jember, serta dampaknya terhadap kualitas kehidupan rumah tangga pasangan muda. Pernikahan pada usia dini sering kali dianggap negatif karena pasangan dinilai belum siap secara psikologis, ekonomi, dan sosial. Namun, temuan di lapangan menunjukkan bahwa beberapa pasangan muda mampu membangun keluarga sakinah melalui sikap saling pengertian, penerimaan terhadap kekurangan masing-masing, pemenuhan tanggung jawab sesuai peran, serta adanya dukungan dari keluarga dan masyarakat sekitar. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik observasi dan wawancara mendalam terhadap lima pasangan pelaku pernikahan usia dini. Hasil penelitian menunjukkan bahwa ketahanan rumah tangga yang sakinah dapat terbentuk apabila terdapat komitmen bersama, komunikasi yang efektif, serta penerapan nilai-nilai Islam sebagai pedoman hidup. Dengan adanya kesiapan mental dan spiritual, pernikahan usia dini dapat dijalani secara positif dan berkontribusi terhadap terbentuknya rumah tangga yang harmonis dan stabil. Penelitian ini menegaskan bahwa faktor kesiapan, bukan semata usia, menjadi kunci dalam mewujudkan pernikahan yang berkualitas.]